The Paracoccus denitrificans NarK‐like nitrate and nitrite transporters—probing nitrate uptake and nitrate/nitrite exchange mechanisms. Issue 1 (27th October 2016) - Goddard, Alan D.; Bali, Shilpa; Mavridou, Despoina A.I.; Luque‐Almagro, Victor M.; Gates, Andrew J.; Dolores Roldán, M.; Newstead, Simon; Richardson, David J.; Ferguson, Stuart J.
Summary: Nitrate and nitrite transport across biological membranes is often facilitated by protein transporters that are members of the major facilitator superfamily. Paracoccus denitrificans contains an unusual arrangement whereby two of these transporters, NarK1 and NarK2, are fused into a single protein, NarK, which delivers nitrate to the respiratory nitrate reductase and transfers the product, nitrite, to the periplasm. Our complementation studies, using a mutant lacking the nitrate/proton symporter NasA from the assimilatory nitrate reductase pathway, support that NarK1 functions as a nitrate/proton symporter while NarK2 is a nitrate/nitrite antiporter. Through the same experimental system, we find that Escherichia coli NarK and NarU can complement deletions in both narK and nasA in P. denitrificans, suggesting that, while these proteins are most likely nitrate/nitrite antiporters, they can also act in the net uptake of nitrate. Finally, we argue that primary sequence analysis and structural modelling do not readily explain why NasA, NarK1 and NarK2, as well as other transporters from this protein family, have such different functions, ranging from net nitrate uptake to nitrate/nitrite exchange. Abstract : NarK‐like proteins have been proposed to function either as nitrate/proton symporters or as nitrate/nitrite exchangers. According to functional studies, NasA and the NarK1 domain of NarK in Paracoccus denitrificans are examples of the former and the NarK2 domain of the latter. Structural data are not readily consistent with this classification thus the possibility that all NarK‐like proteins have a nitrate/nitrite exchange function, with nitrite being imported by the nitrite channel NasH when required, is discussed.